2021
DOI: 10.22146/jcoemph.58535
|View full text |Cite
|
Sign up to set email alerts
|

Barrier to health protocol adherence during exercise among youth in the COVID-19 pandemic era

Abstract: Physical inactivity is one of the non-communicable disease risk factors. This study discusses how the Coronavirus Disease-2019 (COVID-19) has increased the leisure time, including among youth. The health promotion to improve the physical activities of youth is needed. This study aimed to analyze the level of compliance among Indonesian people particularly the young adults towards health protocol during exercise and conduct an intervention accordingly. This study used an action research design, with consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Afro et al (2020) found that 19% of their participants had to at times remove their masks due to difficulties breathing, also they showed barrier perception affected the variable of compliance with health protocols by 10.2% (p = 0.001). Silvano et al (2021) showed that 39.3% of participants did not use their masks when exercising.…”
Section: Discussionmentioning
confidence: 99%
“…Afro et al (2020) found that 19% of their participants had to at times remove their masks due to difficulties breathing, also they showed barrier perception affected the variable of compliance with health protocols by 10.2% (p = 0.001). Silvano et al (2021) showed that 39.3% of participants did not use their masks when exercising.…”
Section: Discussionmentioning
confidence: 99%